2017
DOI: 10.1038/s41598-017-04555-2
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 overexpression contributes to Cadmium-induced death in rat proximal tubular cells via parthanatos and the MAPK signalling pathway

Abstract: Parthanatos is a newly discovered form of PARP-1-dependent programmed cell death. It has been reported to play an important role in several cancer or tumour cells; however, few studies have been performed in normal cells. Cadmium is a highly toxic pollutant and is reported to induce autophagy and apoptosis in multiple cell types. Although cadmium toxicity induces cell death, the underlying mechanism is not fully understood. Therefore, in this study we aimed to investigate the mechanism of Cadmium -induced cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The level of caspase-3 was increased as was the level of caspase-9 by GNP-HER2 treatment. In addition, expressions of PARP31 and DFF45 (ICAD),32 which are substrate proteins of caspase-3, were reduced or fragmented by GNP-HER2 treatment. These results suggest that caspase-3 plays a more important role in the final stage of apoptosis, although several proteins are involved in cellular apoptosis induced by GNP-HER2.…”
Section: Discussionmentioning
confidence: 99%
“…The level of caspase-3 was increased as was the level of caspase-9 by GNP-HER2 treatment. In addition, expressions of PARP31 and DFF45 (ICAD),32 which are substrate proteins of caspase-3, were reduced or fragmented by GNP-HER2 treatment. These results suggest that caspase-3 plays a more important role in the final stage of apoptosis, although several proteins are involved in cellular apoptosis induced by GNP-HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Late apoptotic cells: the cells nuclear chromatin appear orange-red and showed shrinkage-like or fragment-like structures. Non-apoptotic dead cells: the cells nuclear chromatin appears red and shows a normal structure” 44 .…”
Section: Materals and Methodsmentioning
confidence: 99%
“…Previous reports have shown that Cd induces the MAPK signaling pathway in lung adenocarcinoma cells and rat proximal tubule cells. 42,43 Therefore, the Cd-induced increase in SLC2A2 transcription may involve the MAPK pathway, rather than MEF2A.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that Cd induces poly(ADP-ribose) polymerase 1 (PARP-1)-related renal cell toxicity. 43 It has also been reported that the overexpression of PARP-1 consumes ATP. 49 A reduction in intracellular ATP may change the cellular structure and various physiological functions, leading to cell death.…”
Section: F I G U R Ementioning
confidence: 98%